BETWEEN EMOTION AND LEGAL CERTAINTY: AN ANALYSIS OF EXPLICIT (SHARIH) AND IMPLICIT (KINAYAH) EXPRESSIONS IN DIVORCE FROM AN ISLAMIC FAMILY LAW PERSPECTIVE - Arwinni Eka Putri Ahmad; Abdul Syatar; Fatmawati (UIN Palopo, 2026)
Domestic conflicts triggered by emotional outbursts often lead to the utterance of statements that may have legal consequences for the continuity and stability of marriage. In Islamic law, divorce pronouncements (talaq) are classified into ṣarīḥ (explicit) and kināyah (implicit) expressions, each carrying distinct legal implications. A ṣarīḥ expression is understood as an explicit declaration that unequivocally indicates divorce and therefore does not require the presence of intention (niyyah) for its legal validity. In contrast, a kināyah expression consists of indirect or ambiguous wording whose legal effect depends on the existence of the speaker's intention to divorce. The legal issue arises when such expressions are uttered in a state of anger or emotional distress, raising questions regarding their validity and legal force. This study aims to analyze the concepts of ṣarīḥ and kināyah expressions in Islamic family law, examine the role of intention in determining the validity of divorce, and explore their relevance in contemporary family practices. This research employs a normative legal approach using jurisprudential, juridical, and conceptual perspectives. The data are analyzed descriptively and qualitatively based on the sources of Islamic law, statutory regulations, and relevant scholarly literature. The findings demonstrate that the distinction between ṣarīḥ and kināyah expressions serves as an important instrument in maintaining a balance between legal certainty and substantive justice in divorce cases. Furthermore, an emotional state does not automatically invalidate the legal consequences of a divorce pronouncement; rather, its legal effect should be assessed based on the level of awareness, the surrounding context, and the speaker's intention. Therefore, a comprehensive understanding of divorce expressions is essential to ensure that the determination of marital status is not based solely on the formal wording of the pronouncement but also takes into account psychological, social, and family welfare considerations.